2015
DOI: 10.3109/00365521.2015.1121515
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive assessment of the prognosis of pancreatic cancer: peripheral blood neutrophil–lymphocyte ratio and immunohistochemical analyses of the tumour site

Abstract: Our results demonstrated the validity of the NLR by IHC analyses and we determined that a higher value of NLR is a trustworthy prognostic factor for patients with PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 36 publications
0
41
1
Order By: Relevance
“…Screening and application of eligibility criteria produced 8 studies and a total of 1519 patients for analysis. [12][13][14][15][16][17][18][19] The characteristics of the included studies are shown in Table 1. Only one study did not find a statistically significant association between a high NLR and OS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening and application of eligibility criteria produced 8 studies and a total of 1519 patients for analysis. [12][13][14][15][16][17][18][19] The characteristics of the included studies are shown in Table 1. Only one study did not find a statistically significant association between a high NLR and OS.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Half of the included studies failed to comment on the presence of biliary obstruction or instrumentation, whilst the rest simply commented that it was used selectively. 14,[17][18][19] Only half of the studies attempted to control for infection by excluding septic patients and therefore does limit the validity of their results. [14][15][16][17] Across the studies pooled in the meta-analysis, there was a significant amount of heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NLR may be a novel marker for survival (23,24). As expected, NLR was also identified as a prognostic factor in patients with PDA following surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…These reports indicated the potential of CHST15 and CD44 as prognostic factors in patients with PDA following surgical resection. Previous reports have indicated that low neutrophil-to-lymphocyte ratios (NLRs) and low carbohydrate antigen 19–9 (CA19-9) levels may be associated with significantly improved prognoses in patients with PDA (23,24). Thus, the present study analyzed NLRs and CA19-9 levels in the peripheral blood and the expression of CHST15 and CD44 in PDA tissue from surgical specimens as prognostic factors for patients with PDA following surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…Both serum sCD163 level and tumoral CD163 expression showed poor prognosis in different types of cancer [17][18][19]. It is necessary to explore whether these two parameters were connected.…”
Section: Correlation Of Serum Scd163 Level With Tumoral Cd163 Expressmentioning
confidence: 99%